Direct Shoot Regeneration from Mature Leaf Explants of Sphaeranthus indicus L., A Multipurpose Medicinal Plant - Kumar Vemunoori, Venugopal Rao Kokkirala, Pavan Umate and Sadanandam Abbagani*, Rajesh Yarra, Mahender Aileni, Anil (Journal of Phytology, 2010)
A rapid and reproducible protocol for in vitro regeneration of Sphaeranthus indicus (Asteraceae), a medicinal herb has been established. Leaf segments isolated from mature plants were cultured on MS medium with different concentrations of 6-benzyladenine (2.2, 4.4, 6.6 and 8.8 µM) or kinetin (1.3, 2.3, 4.6 and 6.9 µM). Inclusion of IAA into BA supplemented medium triggered a high frequency of regeneration response from leaf explants. Maximum number of shoots (12 ±1.15) with highest shoot length (3.0 ±0.73) were obtained directly (without intervening callus phase) from the leaf explants using combination of BA (4.4 µM) and IAA (1.71 µM) within 3-4 week of culture. The elongated shoots were rooted on MS medium fortified with IBA (2.46 µM).The regenerated plantlets were successfully hardened on earthen pots after proper acclimatization under greenhouse conditions.